Prussian blue analogues and their derived nanomaterials for electrocatalytic water splitting - Cao, Li-Ming; Lu, David; Zhong, Di-Chang; Lu, Tong-Bu (Coordination chemistry reviews, 2020)
•Core scientific challenges in electrocatalytic water splitting were discussed.•Prussian blue analogues (PBAs) as electrocatalysts for water splitting.•PBA derived nanomaterials as electrocatalysts for water splitting.•Perspectives for PBA-based water-splitting electrocatalysts were put forward. The electrocatalytic water splitting is considered as a prospect meaning to address the urgent energy and environmental problems. However, the electrocatalytic water splitting is greatly limited by the high overpotentials of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Especially, OER involves a complex multistep proton-coupled electron transfer process, which demands a high overpotential to accelerate this sluggish oxygen evolution kinetics. The high overpotentials for OER significantly decrease the efficiency of the overall water splitting. The OER half reaction has thus become the bottleneck of electrocatalytic overall water splitting. It is vital to synthesize highly active electrocatalysts to reduce the activation energy of the reaction and accelerate the generation of H2 and O2, thereby improving the efficiency of the overall water splitting. Prussian blue analogues (PBAs) are representative cyanide-based coordination polymer materials. PBAs possess open framework structures, large specific surface areas, adjustable metal active sites and uniform catalytic centers, showing promising application in electrocatalytic water splitting. Besides, benefiting from the unique structural features of PBAs, their derived electrocatalysts also have large specific surface areas and uniform active sites. Moreover, PBAs can serve as carbon and nitrogen sources. The doped N can regulate the electronic structure of surface active sites, enhancing the intrinsic activity of electrocatalysts. Therefore, the PBA-derived electrocatalysts also exhibit good catalytic performance for water splitting. In this review, we not only summarize the most recent advances on PBAs and their derivatives as electrocatalysts for water splitting, but also conclude the core scientific challenges faced in water splitting. Finally, we provide perspectives for the future research in this field, including catalyst design, catalytic system establishment and so on.